Outcome for children following admission to hospital with a first episode of heart failure, due to heart muscle disease, in the ventricular assist device (VAD) era. (12th July 2019) - Rico-Armada, Andres; Crossland, David S.; Coats, Louise; Reinhardt, Zdenka; Hermuzi, Anthony; Seller, Neil; Hasan, Asif; O'Sullivan, John J.
Abstract: Aims: Most reports on the outcome of children who present with heart failure, due to heart muscle disease, are from an era when ventricular assist devices were not available. This study provides outcome data for the current era where prolonged circulatory support can be considered for most children. Methods & Results: Data was retrieved on 100 consecutive children, who presented between 2010 – 2016, with a first diagnosis of unexplained heart failure. Hospital outcome was classified as either death, transplantation, recovery of function or persistent heart failure. Median age at presentation was 24 months and 58% were < 5 years old. Hospital mortality was 12% and 59% received a heart transplant. Most, 79%, of the transplants were carried out on patients with a device. Recovery of function was observed in 18% and 10% stabilised on oral therapy. Eighty-four percent of the deaths occurred in the <5 year old group. Shorter duration of support was associated with survival (34 days in survivors versus 106 in non-survivors, p = 0.01) and 72% were on an assist device at time of death. Conclusion: Heart failure in children who require referral to a transplant unit is a serious illness with a high chance of either transplantation or death. Modifications in assist devices will be required to improve safety, especially for children < 5 years old where the donor wait may be prolonged. The identification of children who may recover function requires further study.